Divorce in Contemporary Islamic Law and the Challenges of its Application in Indonesia in the Context of Contemporary or Modern Society - Mugni (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
This field research uses a qualitative approach, the analysis method uses sociological descriptive analysis, primary and secondary data research, data collection through observation, interviews and documentation. Based on the results of the study, divorce is a legal process that ends a marriage relationship between husband and wife. The decision to divorce can be caused by various factors, first one of the parties commits adultery and heinous acts that are difficult to cure, second one of the parties leaves the other party for 2 (two) consecutive years without the permission of the other party and without valid reasons, third one of the parties gets a prison sentence of 5 (five) years, Fourth One of the parties commits cruelty and persecution Fifth One of the parties gets a disability or illness with the result that he cannot carry out his obligations as a husband or wife, Sixth Between husband and wife there are continuous disputes that there is no hope that they will live in harmony again, seventh The husband violates the taklik talak, eighth The change of religion that causes disharmony in the household. In its development divorce from the perspective of contemporary Islamic law (modern society) demands that Indonesian Muslim husbands and wives, if "forced" to divorce, should comply with the rules of Indonesian madhhab law. A husband, if he wants to divorce his wife, should ask for consideration and judgment and then ask for permission to divorce from the ulil amri (court).